1994
DOI: 10.1056/nejm199405053301804
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Low-Fat Diet on the Incidence of Actinic Keratosis

Abstract: In patients with a history of nonmelanoma skin cancer, a low-fat diet reduces the incidence of actinic keratosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(85 citation statements)
references
References 15 publications
0
83
2
Order By: Relevance
“…Subsequently, Black and his colleagues confirmed the stimulatory effect of a high fat diet on UV-induced formation of skin tumors in mice, and they provided evidence for an association of high-fat diets with actinic keratosis and skin cancer in humans (14)(15)(16)(17). Recently, prospective studies indicated that high-fat diets increased the risk of squamous cell carcinomas, and individuals with a high body mass index were at a higher risk of contracting skin cancer than individuals with a low body mass index (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Black and his colleagues confirmed the stimulatory effect of a high fat diet on UV-induced formation of skin tumors in mice, and they provided evidence for an association of high-fat diets with actinic keratosis and skin cancer in humans (14)(15)(16)(17). Recently, prospective studies indicated that high-fat diets increased the risk of squamous cell carcinomas, and individuals with a high body mass index were at a higher risk of contracting skin cancer than individuals with a low body mass index (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized clinical trial, one hundred patients who had already developed one non-melanoma skin cancer were placed on either a normal or a low-fat diet, and followed for 2 years for the development of skin cancer (Black et al, 1995). A low-fat diet was found to reduce significantly the occurrence of BCCs in this randomized, cohort study (Black et al, 1994;Black et al, 1995). However, subsequent observational studies using questionnaires to assess diet failed to find a protective effect of a low fat diet against BCC carcinogenesis (McNaughton et al, 2005).…”
mentioning
confidence: 90%
“…These variables include the ingestion of fat with different compositions in different individuals, differences in caloric intake among different individuals, and differences in gene͞environment͞lifestyle interactions among different individuals. A carefully controlled randomized intervention trial in human subjects indicated that reducing the percentage of fat calories from 39% to 21% of total calories caused a marked reduction in the number of actinic keratoses (precancerous lesions) and nonmelanoma skin cancers (47)(48)(49). Although the latter intervention trial indicates that decreasing the level of dietary fat can inhibit the formation of UV-induced skin tumors in humans (possibly by enhancing apoptosis), even this carefully done study may also be affected by confounding variables such as substances that were added to the diet to replace fat.…”
Section: Table 4 Effects Of Partial Lipectomy (Surgical Removal Of Tmentioning
confidence: 99%